COMPONENTS OF ANTARCTIC PLANTS WHICH INHIBIT SEED GERMINATION (Twelfth Symposium on Polar Biology) - ツジノ, ヤスコ; タザキ, ヒロユキ; ヨシダ, ケンジ; フジモリ, タカネ; モチダ, ユキラ /; TSUJINO, Yasuko; TAZAKI, Hiroyuki; YOSHIDA, Kenji; FUJIMORI, Takane; MOCHIDA, Yukira; OHYAMA, Yoshikuni (National Institute of Polar Research, 1991)
P(論文) The inhibitions of seed germination and microbe growth by extracts of antarctic plants were examined. Assays for non-specific toxin activity of the extracts were also carried out using soybean leaves. Three kinds of mosses, three kinds of lichens and five kinds of algae were extracted with methanol. The methanol extracts were evaporated, and the residues were extracted with chloroform. The chloroform layers and the aqueous layers were subjected to assays. Among them, chloroform extracts of two lichens inhibited seed germination and microbe growth. Purification of these extracts, and structure elucidation of the active components were discussed. departmental bulletin paper